The Effect of Media Cadres Handbook on Breast Cancer and Breast Self-Examination (BSE) on Knowledge and Skills of Health Cadres in Tamansari District, Tasikmalaya City - Sariestya Rismawati; Yulia Herliani; Laila Putri Suptiani (Journal Research of Social Science, Economics, and Management, 2022)
Health promotion about Breast Cancer and its Early Detection can be done by health cadres. There are still many health cadres who do not understand breast cancer and how to detect breast cancer early. The COVID-19 Pandemic conditions that limit direct interaction have limited the process of developing the ability of cadres in this case to increase knowledge, so health education is needed with media that is easy to understand and practical so that it can be used flexibly anywhere and anytime. This cadre handbook has passed due diligence from material experts, media experts and linguists, as well as passed a small-scale test on representatives of health cadres in independent research with the results very feasible to use. Breast Cancer and Breast Self-Examination (BSE) on Cadre Knowledge and Skills. The design used is a quasi-experimental design with a one group pretest-posttest design. The sample in this study was health cadres in Tamansari District, Tasikmalaya City. The sampling technique used is purposive sampling. The research variables are knowledge and skills. The data used are primary data in the form of questionnaire results and observations. Data analysis was carried out using two analytical techniques, namely univariable and bivariable analysis. The bivariable analysis used was to determine the effect of the cadre handbook on knowledge and skills using the Wilcoxon test. There is an effect of cadre handbooks on knowledge and skills of cadres about breast cancer and breast self-examination (p=0.000). The effect of the cadre handbook on breast cancer and Breast Self-Examination (BSE) on the knowledge and skills of health cadres in Tamansari District, Tasikmalaya City.